Internationalization of Banks: Strategic Patterns and Performance - Alfred Slager (SUERF - The European Money and Finance Forum, 2005)
This essay investigates the relationship between the internationalization of banks, profitability and shareholder value. We argue that in general internationalization has not contributed to profitability, and shareholders have not gained by investing in banks with more international activities. A database with internationalization measures is constructed for the 3 to 5 largest banks in 8 countries between 1980 and 2003, leading to a sample of 44 banks. The transnationality index is calculated for each bank, combining foreign assets, foreign income and foreign staff into one index. To examine the relationship between internationalization and performance, we calculated the difference between foreign and domestic profitability. We also investigate if more internationalization is related to more profitability. The key finding is that foreign profitability tends to be lower than domestic, and a negative relationship exists between total profitability and internationalization. Also, a " J-curve" shape appears, suggesting that up to a certain degree of internationalization (roughly 40% of foreign staff, income and assets), costs tend to outrun benefits. A similar pattern emerges for shareholder return: banks that either strongly or moderately increased their internationalization activities generated the lowest shareholder return as a group, while banks that retreated generated the most. For the future, we identify banks which are likely in the near future to reassess their internationalization strategy, either to develop a business model where internationalization activities are a stable and profitable source of income, or where banks refocus their attention to the domestic banking market.
Keywords: F23; F30; G21; L1; 330; internationalization; banking; value creation; performance; Bankmanagement; Internationale Bank; Shareholder Value